THE STUDY OF THE CAUSES OF IRREGULARITY OF CRACKERS QUALITY IN THE CRACKERS INDUSTRY IN JEMBER (Case Study in Crackers Industry in Mangli, Kalisat and Arjasa, Jember) - Elok Sayyidah Balya; Achmad Marzuki Moen’im; Setiadji Setiadji (UPT Penerbitan Universitas Jember, 2012)
Crackers is one of food product which is known for centuries in many forms. Thisis caused by the variety of flavors, and its simple processing. Generally, crackers isprocessed traditionally, so it is not surprising that some crackers producers simply processthem. Crackers is a famous and popular snack for Indonesian. The purpose of this researchis to know the most critical steps during the production and distribution process,identifying the factors that affecting product quality, and to know the best physical andchemical characteristic. The data of this research comes from questionnaire data and checklists of three crackers industry In three residents (Mangli, Kalisat, and Arjasa) in Jember.Organolepticness data and the chemical characteristic data come from the product of thoseregencies. The criterion of product flaw widely spread from the smallest to the biggest.They are thickness, crack, the ripeness and the color. The factors that affect the quality areraw materials, weather, employers, the engine, drying process, and cooking process. Basedon the analysis of organolepticness, it shows that based on the flavor of the crackers, themost favorable crackers is produced in Mangli. Based on the color, the most favorablecrackers is produced in Arjasa. Based on the crispness of the crackers, the most favorablecrackers is produced in Mangli. While the chemical analysis shows the highest watercontent of the crackers is produced in Mangli because the high content of fiber, while thehighest crackers ash content is produced in Arjasa.